Efficacy of Proton Pump Inhibitors vs. H2-Receptor Antagonists in GERD Patients: A Double-Blind RCT - Sajjad Hussain Sabir, Syed Osama Talat, Imran Ahmed Moinuddin, Maira Aslam, Nabeel Sardar Muhammad, Atif Mahmood, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Gastroesophageal reflux disease (GERD) is prevalent globally, necessitating effective therapeutic strategies. This double-blind randomized controlled trial compared the efficacy and safety of proton pump inhibitors